Analysis of Mathematical Representation Ability According to Cognitive style - Saputro, Marhadi; Prihatin, Iwit (STKIP Singkawang, 2023)
The aim of this research is to analyze students' mathematical representation abilities in terms of cognitive style in the multivariable calculus course taught in semester 4 of the IKIP PGRI Pontianak Mathematics Education Study Program. This research is a qualitative descriptive research in the form of case study research. Research subjects were selected based on their cognitive style which was measured using the geft instrument. Selected subjects were then asked to work on mathematical representation ability questions and then interviewed according to these questions. Based on the research results, it was found that students who had a field dependent cognitive style in symbolic representation were able to link symbols with mathematical concepts, in graphical representation they were able to create images in the form of requested graphs, while in verbal representation they were less able to convey ideas effectively orally. or written. Meanwhile, students with an independent cognitive style in symbolic representation have been able to link symbols with mathematical concepts, in graphic representation they have been able to create images in the form of requested graphics, and in verbal representation they have been able to convey ideas effectively.